Occurrence Of Hydrogenetic Ferromanganese Crusts From Deep-Sea Floors In The Western Pacific - Akira Usui (International Marine Minerals Society, 2001)
Occurrence of hydrogenetic ferromanganese crusts has been well documented over inactive seamounts in the central and southern Pacific Ocean. It has been thus believed that the hydrogenetic crusts develop preferentially at water depths between about 800 to 2500 meters. In fact, according to the Manganese Crust Database (F. Manheim, 1988), only two occurrences are known at water depths below 5000 m out of 819 occurrences cited in the database. Unexpectedly, we found typical hydrogenetic ferromanganese crusts from deep-sea floors; 1) outcropping old volcanic basement over the Philippine Sea Plate (abandoned spreading centers and subducting old oceanic crusts) and 2) one from the slope of an abyssal hill in the Central Pacific Basin (Cretaceous deep-sea basin) at water depths ranging between 5200 to 6100 meters. We report their occurrences with submersible observations from Shinkai 6K, physical parameters (such as thickness of crusts about 2-4 cm in maximum), chemical composition, petrology of substrate, and results of Be-10 dating for some samples in comparison with typical Co-rich manganese crusts from the Central Pacific seamounts. The preliminary chemical and mineralogical analyses reveal that they are of typical hydrogenetic origin, and typical of iron-manganese oxide mineral, vernadite, slow and probably continuous growth, and lower content of Co than the Central Pacific seamount crusts. The occurrences and nature of the crusts indicate that deep-sea floors are also optimal for the growth of hydrogenetic crust even at 5000 m water depth or deeper, only if oxygenated deep waters are supplied and the sea-floor morphology keeps stable enough for significant geological time period. Additional details of chemical analyses will be prepared by November and to be shown in the conference.